Common pathological mechanisms and therapeutic strategies in primary Sjogren’s syndrome and primary biliary cholangitis: from tissue immune microenvironment to targeted therapy - Ye, Keying; Yao, Xinyi; Lu, Dingqi; Tan, Chenfei; Wang, Xinchang (Frontiers in Immunology, 2025)
Autoimmune diseases are characterized by their involvement of multiple organ systems and the presence of overlapping clinical manifestations among distinct disease entities. Both primary Sjogren’s syndrome (pSS) and primary biliary cholangitis (PBC) are chronic inflammatory disorders driven by immune-mediated injury to glandular or ductal epithelial cells. Due to shared genetic susceptibility, epidemiological patterns, and pathophysiological mechanisms, these two diseases frequently coexist in clinical practices and demonstrate a common tissue immune microenvironment. Recent advances have greatly enhanced the understanding of pSS and PBC pathogenesis, particularly regarding autoantibody profiles and pro-inflammatory cytokine expression in serum, as well as the functional activity of immune cells within affected tissues. These insights provide new perspectives and potential avenues for the development of targeted therapeutic strategies. This review examines the associations between pSS and PBC, explores the shared immunological pathways involved in disease onset and progression, and summarizes common therapeutic targets within the context of clinical treatment. The goal is to provide a comprehensive perspective that may guide future research and inform improved diagnostic and therapeutic strategies for both conditions.